2011
DOI: 10.1021/ac2018348
|View full text |Cite
|
Sign up to set email alerts
|

Single-Electrolyte Isotachophoresis Using a Nanochannel-Induced Depletion Zone

Abstract: Isotachophoretic separations are triggered at the border of a nanochannel-induced ion-depleted zone. This depletion zone acts as a terminating electrolyte and is created by concentration polarization over the nanochannel. We show both continuous and discrete sample injections as well as separation of up to four analytes. Continuous injection of a spacer compound was used for selective analyte elution. Zones were kept focused for over one hour, while shifting less than 700 μm. Moreover, zones could be deliberat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 53 publications
(62 reference statements)
0
41
0
Order By: Relevance
“…This can be achieved by concentrating various intermediate mobility species to such high concentrations that it is capable of changing the electric field profile according to the Kohlraush Regulating Function (KRF), as is commonly observed in isotachophoresis (ITP) experiments. 4042 …”
Section: Resultsmentioning
confidence: 99%
“…This can be achieved by concentrating various intermediate mobility species to such high concentrations that it is capable of changing the electric field profile according to the Kohlraush Regulating Function (KRF), as is commonly observed in isotachophoresis (ITP) experiments. 4042 …”
Section: Resultsmentioning
confidence: 99%
“…The functionality of the device was demonstrated by detection of a stacked fluorescent species with a LOD on the 100 pM level and by the analysis of explosives and an herbicide in river water without sample pretreatment. Quist et al investigated microchip systems with nanochannel‐induced concentration polarization and found that the border of the formed depletion zone has the properties of an ITP boundary. Experiments (using a fluorescence microscope in combination with a digital camera) with 2 mM lithium carbonate (pH 10.6) as the BGE, fluorescing model analytes (fluorescein, 6‐carboxyfluorescein, FITC‐leucine, and FITC‐glutamate) and acetate as nonfluorescent spacer confirmed formation of separate zones of ITP nature.…”
Section: Instrumentation and Techniquesmentioning
confidence: 99%
“…Chips were fabricated in Pyrex wafers using standard lithography techniques and dry etching with an SF 6 /Ar plasma. Details of the chip fabrication procedure can be found in the Supporting Information of ref 17. The chips had microchannels with 1.7 μm depth and 20 μm width.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…16 Recently, we introduced depletion zone isotachophoresis (dzITP), using a nanochannel-induced depletion zone at the border of which analytes were focused and separated into adjacent zones. 17 As the depletion zone replaces the terminating electrolyte that is used in conventional ITP, dzITP is a single-electrolyte isotachophoretic method, which is an important simplification. Moreover, dzITP exhibits great versatility, because analyte zones can be precisely positioned by tuning the balance between fluid flow through the separation channel and depletion zone growth.…”
mentioning
confidence: 99%